Socio-humanitarian knowledge and education: development paradoxes - Novik, Evgeny K. (Journal of the Belarusian State University. Sociology, 2019)
The problems of the development of the education system in the Republic of Belarus are considered, omissions and miscalculations of the reform of the social humanitarian block of disciplines, connected with entering the Bologna process, the transition to centralized testing, the modular system of education are analyzed. The author makes proposals on improving the current system of higher education.